Instrumentos empregados no Estado Democrático de Direito para persuadir o cidadão a respeito de sua responsabilidade tributária: coerção, incentivo e educação - Silva, Robson de Souza (2018)
The dynamic democratic society that we live in leads us to consider other ways that conduct to legal models that point to a new way of using the law, not only its pragmatic framework, that is to say, coercion. Thus, in order for the state to acquire a positive image and be seen as a source of contemporary administration, it must employ techniques that are diverse from the majority until then used. In this way, the sanctioning system of conducts as the only form of social adjustment is no longer a safe haven, since it has become an inappropriate tool and of uncertain legal efficiency. Along these lines, a critical analysis regarding the breakdown of this model and a discussion about the use of alternative methods of raising awareness. Thus, the use of coercion, whether in the political question, in its transverse forms of collection, or in the tax question, with the erosion in the lack of legal certainty with the variation of the values of its fines and by term, in the criminal court, imposed on cases of unlawful taxation, where, as is inferred from the study of some of its principles, its use for this type of purpose goes beyond its basic dictates, since there is a deviation from its purpose, since it would be exercising a function of tax collector, which completely distances him from his primary function. Such tools only ratify the need for model breaking. With this thought of fusion, the opportunity of employment of the incentive institute arises, since it is a stimulating technique for the practice of good conduct. Consequently, reducing the state's wear and tear on measures that involve unpopular themes and sometimes difficult to accept. It is important to mention the use of this tool, considering the possibility of reverse effects. Finally education, sine qua non condition for a change of attitude in any area. Source of best alternative to developing a fiscal conscience. Federated entities have a number of programs in this respect, which, well employed, have the potential to break standards. In this way, it is concluded that the State, even with an apparent paradoxical bias, finds support in the normative text that forms the legal framework of the society of law to make use of the most diverse tools of persuasion direct and indirect, aiming at promoting the citizen's awareness that his tax responsibility should be treated as a burden to live in a democratic society under the pallium of the rule of law.